Contemporary Socio-Economic Concepts of the Market - Вадим Валерьевич Радаев (Journal of Economic Sociology, 2010)
The paper is devoted to the modern approaches to the market explanation that exist in the contemporary economic sociology. A wide research program with several directions is under focus here. The market is analyzed from the positions of different current socio-economic approaches: ecological, structural, new institutional, political economics, socio-cultural, phenomenological and political cultural.